Before David - Gonzalez, Melissa Saucedo; Gonzalez, Melissa Saucedo (Academic Video Online, 2015)
A short documentary film about pre-partum depression, its symptoms, and the difficulties it poses when a woman is going through extreme physical and emotional changes.The film reflects on the constructed image of the pregnant woman in Western society, and on the expectations placed on women at a time when they are undergoing an extreme physical and emotional transformation. It challenges the prevalent idea that pregnancy is an antidote to depression in women, and that symptoms of depression tend to occur only after birth, as postpartum depression. Before David aims to create awareness and start a conversation about women's mental health during pregnancy, and about the dangers of antenatal depression for women and their newborns.